Chitosan- hypothalamic hormonal analogue nanoconjugates enhanced the reproductive performance in Indian major carp, Labeo rohita - Malik, Mohd Ashraf; Gupta, Subodh; Varghese, Tincy; Jahageerdar, Shrinivas; Nayak, Sunil Kumar; Reang, Dhalongsaih; Bhat, Irfan Ahmad; Mahadevaswamy, Chandan Gowramma; Chuphal, Nisha; Dar, Showkat Ahmad; Prabhakaran, Arya (Frontiers in Marine Science, 2023)
The current study reports the potential of chitosan nanoparticles for the efficient delivery of hypothalamic hormonal analogue in Labeo rohita, aiming to improve reproductive performance. Here salmon gonadotropin-releasing hormone analogue (sGnRH-a) was conjugated with chitosan nanoparticles (ChN-sGnRH-a) to evaluate its efficiency in enhancing the reproductive gene expression, hormones as well as the overall reproductive output in L. rohita. A total of 54 pairs of brooders were selected and divided into six treatments viz; C0: Negative Control (fish injected with bare chitosan nanoparticles), C: Positive Control (fish injected with Gonopro-FH®, a commercially available inducing hormone, at a dose of 0.2 ml/kg body weight of fish), T1: fish injected with ChN-sGnRH-a at a dose of 0.2 ml/kg, T2: T1 + 10 mg/ml domperidone, T3: fish injected with ChN-sGnRH-a at a dose of 0.1 ml/kg, T4: T3 + 10 mg/ml domperidone. In T2 and T4 treatments, serum hormones, Testosterone (T); Estradiol (E2); Vitellogenin (Vtg); and 17α, 20β-dihydroxyprogesterone (17α, 20β-DHP) showed the sustained elevation. The means of reproductive traits like fecundity, fertilization rate, pseudo-gonadosomatic index and spawning rate were significantly (P<0.05) higher in T2 treatment, while no significant difference was found between C and T4 treatment. The mRNA expression level of follicle-stimulating hormone (fshβ), luteinizing hormone (lhβ) and their cognate receptors was significantly better in T2 treatment, while no significant difference was found between T4 and C treatments. Further, the histological analysis of ovaries showed increased post-ovulatory follicles in C, T2 and T4 treatments. The results indicate that ChN-sGnRH-a could help in reducing the recommended dose of sGnRH-a without affecting the reproductive performance in L. rohita females. The sustained releasing mechanism of this formulation may be used as an induced breeding strategy in female L. rohita broodstock.